Sleep Quality, Daytime Sleepiness, and Circadian Rhythm Characteristics in Chronic Kidney Disease: A Cross-Sectional Study Across Disease Stages - Harun Yetkin; Mehmet Fatih Uzanulu; Onur Selçuk Yiğit; Zeynep Dilara Yetkin; İrem Dikilitaş; Hacı Mehmet Çitil; Hacı Bayram Berktaş; Mehtap Karaaslan (The International Journal of Psychiatry in Medicine, 2026)
Objective To compare sleep quality, daytime sleepiness, and circadian rhythm characteristics across clinically defined chronic kidney disease (CKD) groups and to examine their relative contribution to global subjective sleep quality. Method This two-center, cross-sectional study enrolled 344 adults with CKD (response rate: 96.6%) from nephrology settings in Turkey. Participants were classified into three groups: mild-to-moderate CKD (KDIGO stages 2-3; n = 133), advanced CKD without dialysis (stages 4-5; n = 37), and dialysis-dependent CKD (stage 5D; n = 174). Sleep quality, daytime sleepiness, and circadian rhythm parameters were assessed using the Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), and Munich Chronotype Questionnaire (MCTQ). Hierarchical regression identified predictors of PSQI global scores. Results ESS total scores were significantly higher in the dialysis-dependent group compared with both other groups (ε 2 = 0.182, the only large effect size), whereas PSQI global scores were paradoxically lower in this group (adjusted P = 0.021). Biological chronotype (MSFsc) did not differ across groups. In hierarchical regression, ESS (β = 0.525) and dialysis-dependent status (β = −0.318) were the only significant predictors of PSQI global scores, with sleep–wake variables adding 24.3% explained variance beyond demographic and clinical factors. Conclusions CKD-related sleep–wake burden is more prominently reflected in daytime sleepiness and social–circadian disorganization than in global subjective sleep quality. Assessment of daytime sleepiness may improve recognition of sleep–wake dysregulation in nephrology settings.